Usulan Arsitektur Enterprise usaha Penyelengara Acara kecil menengah pada zaman Industry 4.0 pandemi - Daniel Avian Karjadi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Covid-19 pandemic affects businesses around the world and the most impacted are small and medium event organizer business (SMB EO) that usually having social gathering event participated by a few hundred participants only. Digital transformation must be executed immediately to adapt to the conditions utilizing Industry 4.0 technology especially in recent pandemic era. This paper study the enterprise architecture design of SMB EO utilizing Industry 4.0 to survive in pandemic era and beyond. The enterprise architecture based on Togaf framework consists of business, application, information, and technology architecture is decribed in this paper. Small business doesn’t have the big capital on investing in technologies and during pandemic where certain technology is scarce may cause the business to be left behind. Choice of utilizing public social media and cloud providers according to the architecture is the key. Once the technology is adopted, business is digitalized then business can be ready to face future metaverse business model.